(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To compare the functional and radiological results of locking plate versus shortened interlocking nail for treating extra-articular distal tibia fractures. Methods: This randomized trial was conducted in Department of Orthopaedics, Lahore General Hospital from 25th June 2017 to 25th July 2019.All patients of distal tibia fractures fulfilling the inclusion criteria were randomly and equally divided into group A(shortened interlocking nail) and group B(anatomically contoured distal tibial locking plate). Post operatively functional outcome was determined by assessing ankle and knee range of motion. Radiological union was assessed through callus formation on X ray AP and Lateral view. The time of radiological union and range of motion in both groups were compared and chi square test was applied to note any statistical significance with P value of < 0.05 was considered significant. Results: Total 24 patients were equally divided into two groups A and B with 12 patients in each group. The mean age of group A was 22.5 years(range 20 to 34.5 years) while group B had mean age 31 years(range 22 to 35 years).In group A all the patients were male. Group B had 1(8.3%) female patient. Majority(91.6%,n=11) of patients in group A regained normal range of motion of ankle and knee at final follow up. In group B the normal ankle range of motion was noted in 8(66.6%) patients. Non union was documented in 1(8.3%) patient in group A and 3(25%) patients in group B. The functional and radiological outcome was significantly better in interlocking nail group than locking plate group(P value of < 0.05). Conclusion: Extra articular distal tibia fractures treated with shortened intramedullary nail produced better functional and radiological results than locking plate. Shortened intramedullary nail should be the treatment of first choice to treat these fractures.